Plant height is the main factor driving forage yield of Poa species under different row spacings and seeding rates in the Qilian Mountains - Wang, Xiaojun; Wang, Jinlan; Li, ERenCuo; Guo, Yani; Li, Wen (Frontiers in Plant Science, 2025)
Scientific and reasonable planting densities are crucial for Poa species forage production. However, the optimal row spacing and seeding rate for Poa species cultivation, and the effects of row spacing and seeding rate on Poa species forage yield in the Qilian Mountains remain unclear. In the current study, P. sinoglauca Ohwi., P. crymophila Keng, P. pratensis L. var. anceps Gaud, and P. pagophila Bor were selected as study materials, and a split field experiment designed with row spacing as the main factor and seeding rates as the sub-factor was conducted to study the effects of different row spacings and seeding rates on the agronomic traits and forage yield benefits of Poa species. The main plots were designed with different row spacings of 15 cm (R1), 30 cm (R2), and 45 cm (R3), and the subplots were designed with different seeding rates of 7.0 kg·hm-2 (S1), 12.0 kg·hm-2 (S2), and 17.0 kg·hm-2 (S3). A subsection structural equation model was used to analyze the influence process and path coefficients of row spacing, seeding rate, and the interaction between row spacing and seeding rate on the yield of Poa species, and the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) was used to comprehensively assess the agronomic traits and forage yield of the experimental varieties. Our results showed that row spacing significantly affected the plant height, tiller number, fertile tiller number, and forage yield of the four Poa species, while seeding rate and interaction between row spacing and seeding rate had significant effects on the forage yield of the four Poa species. The highest forage yields of P. sinoglauca (6709.1 kg·hm-²) and P. crymophila (7471.3 kg·hm-²) were recorded for a row spacing of 30 cm and seeding rate of 17 kg·hm-², and the highest forage yields of P. pratensis L. var. anceps (9469.0 kg·hm-²) and P. pagophila (8152.7 kg·hm-²) were recorded for a row spacing of 30 cm and seeding rate of 12 kg·hm-². Structural equation modeling indicated that row spacing, seeding rate, and the interaction between row spacing and seeding rate primarily affected the forage yield of Poa species by affecting plant height. Our research provided optimal sowing and row spacing for Poa species depending on the species to optimize forage production in the southern Qilian Mountains and similar areas.